Menjadi “Filosof Muslim” di Media Sosial: Referensi dari Husein Ja’far Al-Hadar - Husin Lubis, Zakaria (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
This article is of the view that the presence of philosophy in cyberspace, especially YouTube, has eliminated the "heavy side" of philosophy. Philosophy is constructed in an entertainment style that is easy to watch, even though it cannot necessarily be understood and interpreted as it should be. The emergence of philosophy on YouTube has succeeded in establishing the authority of philosophers for the individuals who popularized it. Research data was explored from Husein Ja'far Al-Hadar's YouTube channel. To facilitate research, the research question was asked about the process of "becoming a philosopher" in the world of YouTube. Research findings suggest that the process of becoming a Muslim philosopher on YouTube is formed through the number of followers and consistency in discussing philosophy. Then, authority is strengthened by social attributes, such as educational background, social status and knowledge of Islamic philosophy. Lastly, the authority of Muslim philosophers formed through YouTube makes philosophy not express its true form because it exists as entertainment which is contradictory to the orthodoxy of Islamic philosophy.Keywords: Muslim Philosopher, Youtube, Authority and Husein Ja'far.